Particle reinforcement-retention system, reinforced high-performance inorganic fiber foam molding paper-based material as well as preparation method and application of reinforced high-performance inorganic fiber foam molding paper-based material
By adopting the particle reinforcement-retention system in high-performance inorganic fiber foam molding technology, the problems of uneven fiber dispersion and poor retention of enhancement additives are solved, and the paper sheet strength and filler retention rate are significantly improved. A high-performance foam molded inorganic fiber paper-based material was obtained.
Patent Information
- Application Number
- CN202411399251.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
AI Technical Summary
In high-performance inorganic fiber foam molding technology, the smooth surface and inert properties of the fiber lead to uneven fiber dispersion and poor retention of reinforcement additives, resulting in low paper sheet strength and filler retention.
The microparticle reinforcement-retention system is adopted to improve the cross-linking effect on the fiber surface through the combination of organic binder, inorganic cross-linking agent and fiber wetting agent, and a rich pore structure and fiber orientation structure are formed through foam molding technology.
The structural strength and surface uniformity of foam-formed inorganic fiber paper sheets were significantly improved, the filler retention rate increased from 75% to 87%, and lightweight, rich pore structure and high temperature resistance were obtained after sintering.
Smart Images

Figure CN119465689A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance inorganic fiber composite materials, and relates to a particle reinforcement-retention system, a reinforced high-performance inorganic fiber foam molding paper-based material, and a preparation method and application thereof. Background Art
[0002] High-performance inorganic fibers such as quartz fiber, alumina fiber, aluminum silicate wool, etc. have excellent high temperature resistance and insulation properties. High-performance inorganic fiber paper-based materials are usually used as fiber structure reinforcement to prepare high-performance inorganic fiber reinforced silica aerogel composites, such as ceramic fiber reinforced silica aerogel composites (Li Mingming, Wang Kunjie, Zhang Xiaohu. Research Progress of Fiber-Reinforced SiO2 Aerogel Composites [J]. New Chemical Materials, 2017, 45(03): 19-21.). However, the high-performance inorganic fiber has a large aspect ratio and a smooth and inert fiber surface, which limits the fiber dispersion and the retention effect of the reinforcing agent in the traditional wet forming process. The inorganic fiber surface has few hydrogen bonds, and it is difficult for the organic binder to actively cross-link on the fiber surface. The addition of organic binders to the pulp has almost no reinforcing effect on the inorganic fiber paper (Cao Qiping. Research on the Papermaking Performance and Forming Mechanism of Long Fibers [D]. Qilu University of Technology, 2016.).
[0003] Although the microparticle retention system can improve the retention of fillers and fibers during wet forming, it will seriously reduce the drainage rate and the surface uniformity of the paper sheet (Wang Jin, Zhang Dongji, Guo Yongwei, et al. On the application of microparticle retention system in cultural paper production [J]. China Paper Industry, 2006 (11): 65-67.), and has little effect on the strength enhancement of the paper sheet. A system with both enhancement and retention effects is needed to improve the strength of inorganic fiber paper sheets. In addition, the high-performance inorganic fiber paper-based materials formed by wet forming are usually traditional 2D paper sheet structures with high density, poor uniformity, and a poor pore structure, which are not suitable as structural reinforcements for high-performance inorganic fiber aerogel composites.
[0004] Foam forming technology uses foam instead of water as a carrier for fiber dispersion. The adhesion and physical barrier effect of bubbles on fibers can reduce the probability of high-performance fibers flocculating and entangled in the foam slurry. After dehydration and defoaming, the ruptured bubbles leave a rich pore structure and fiber orientation structure inside the paper sheet. Foam forming technology is a new paper sheet forming technology suitable for the dispersion and forming of high-performance inorganic fibers (Yang Huikang, Ding Nengxin, et al. Research on foam forming technology of alumina fiber [J]. China Papermaking, 2023, 42(3): 78-86.). However, in the process of high-performance inorganic fiber foam forming, due to the smooth surface, inertness and small overlap area between fibers of inorganic fibers, the strength and filler retention rate of inorganic high-performance fiber foam forming paper base materials need to be solved urgently. Summary of the invention
[0005] In order to solve the shortcomings of the above high-performance inorganic fiber foam molding technology, the primary purpose of the present invention is to provide a microparticle reinforcement-retention system.
[0006] Another object of the present invention is to provide a method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material.
[0007] Another object of the present invention is to provide a reinforced high-performance inorganic fiber foam forming paper-based material.
[0008] Another object of the present invention is to provide an application of a reinforced high-performance inorganic fiber foam forming paper-based material.
[0009] The purpose of the present invention is achieved through the following technical solutions: A particle reinforcement-retention system is composed of an organic binder, an inorganic crosslinking agent and a fiber sizing agent, wherein the mass ratio of the organic binder, the inorganic crosslinking agent and the fiber sizing agent is 1-10:5-15:0.1-5, preferably 5-8:6-10:0.1-2, and more preferably 5:10:1.
[0010] Preferably, the organic binder is carboxymethyl cellulose (CMC) or hydroxypropyl cellulose (HPC), the inorganic crosslinking agent is aluminum sol or silica sol, and the fiber sizing agent is at least one of anionic polyacrylamide (APAM), polyethylene oxide (PEO), and cationic polyacrylamide (CPAM).
[0011] A method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material using a microparticle reinforcement-retention system comprises the following steps: (1) Dispersing inorganic fibers, fiber dispersant, microparticle reinforcement-retention system and water uniformly, adding fiber dispersant and surfactant and mixing uniformly to obtain a foaming initial solution; (2) The initial foaming liquid is transferred to the foaming device, and the foam slurry is obtained after a certain stirring speed and time. The foam slurry is then injected into the rapid prototyping device, and the wet paper web is obtained after vacuum dehydration and defoaming. After pressing and drying, the reinforced high-performance inorganic fiber foam molding paper base material is obtained.
[0012] Preferably, the inorganic fiber is at least one of alumina fiber, quartz fiber, glass fiber, and aluminum silicate fiber wool, with a fiber diameter of 5-18 μm and a length of 6-36 mm, and the inorganic fiber concentration in the initial foaming liquid is 5-10 g / L; The solid contents of the organic binder, the inorganic crosslinking agent and the fiber sizing agent in the particle retention reinforcement system are 1-10%, 5-15% and 0.1-5% of the absolute dry fiber mass, respectively; The surfactant is at least one of sulfate ester salts, cationic amine salts, cationic quaternary ammonium salts, and betaine polyvinyl alcohol, preferably dodecyl dimethyl ammonium oxide and / or amide gemini quaternary ammonium salts, and the surfactant concentration in the initial foaming liquid is 0.5-5 g / L.
[0013] Preferably, the fiber dispersant is polyethylene oxide, and the added mass is 0.5-2% of the absolute dry mass of the inorganic fiber.
[0014] Preferably, in step (2), the stirring speed is 1500-2000 rpm, and the stirring time is 8-15 min; the air content of the foam slurry is 55%-75%, and the average bubble diameter is 20-100 μm; the dehydration and defoaming vacuum degree is 5-70 KPa, and the squeezing pressure is 5-80 N.
[0015] Preferably, the preparation method further comprises the following steps: impregnating the reinforced high-performance inorganic fiber foam-formed paper-based material in step (2) in an impregnation liquid to obtain an impregnated reinforced high-performance foam-formed inorganic fiber paper-based material, i.e., a rigid high-performance fiber paper sheet; The impregnation liquid is an organic impregnation liquid and / or an inorganic impregnation liquid, the mass concentration of the organic impregnation liquid is 0.1%-5% or 0.1-10g / L, and the mass concentration of the inorganic impregnation liquid is 0.5%-15%; The organic impregnation liquid is at least one of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, polyamide polyamine-epichlorohydrin resin, and polyvinyl alcohol solution; The inorganic impregnation liquid is at least one of aluminum sol, silica sol and sodium silicate solution; The impregnation suction vacuum is 5-50 KPa, the impregnation time is 30-60 min, the paper sheets are air-dried for 20-40 min after impregnation, and the impregnated paper sheets are turned over every 1-5 min during the air-drying process.
[0016] Preferably, fillers are further added in step (1), and finally the reinforced high-performance inorganic fiber foam-formed inorganic fiber paper-based material obtained in step (2) is sintered at a high temperature to obtain a sintered reinforced high-performance foam-formed inorganic fiber paper-based material, i.e., a rigid high-performance fiber paper sheet; The filler is at least one of glass powder, boron carbide, boron nitride, and silica aerogel powder, and the amount of the filler is 5%-30% of the absolute dry fiber mass; The filler is a micro-nano filler.
[0017] Preferably, the high temperature sintering temperature is 700-900° C., and the sintering time is 1-2 h.
[0018] A reinforced high-performance inorganic fiber foam forming paper-based material is prepared by the method.
[0019] The invention discloses an application of a reinforced high-performance inorganic fiber foam-molded paper-based material in the preparation of a silica aerogel composite material.
[0020] The present invention has the following advantages and beneficial effects: (1) The present invention provides a microparticle reinforcement-retention system, which cross-links an organic binder on the surface of inert inorganic fibers to give the foam-formed inorganic fiber paper good structural strength and excellent surface uniformity (such as Figure 4 ab, Figure 5 as shown).
[0021] (2) The microparticle reinforcement-retention system provided by the present invention enables the filler and the fiber to form a "filler-crosslinking agent-fiber" bond during the molding process, and the overall filler retention rate is increased from 75% to 87%, without affecting the surface uniformity of the paper sheet (such as Figure 4 cd shown).
[0022] (3) The present invention uses multi-component functional fillers. Boron nitride with high melting point and poor fluidity is used to in-situ strengthen the inside of the paper sheet to improve the compressive strength of the paper sheet in the Z direction. Glass powder with low melting point and strong fluidity improves its structural strength in the XY direction during the sintering process, ultimately giving the inorganic fiber paper sheet good overall strength ( Figure 6 as shown).
[0023] (4) The base paper under the reinforcement-retention system of the present invention can retain the functional filler on the fiber surface, and can obtain a lightweight and porous structure by cooperating with the sintering process ( Figure 7 a) High temperature resistance ( Figure 7 b) Foam-molded inorganic fiber paper with good strength.
[0024] (5) The foam forming base paper of the present invention has good strength, excellent uniformity and rich pore structure, and is a good fiber structure reinforcement for making inorganic fiber silica aerogel composite materials ( Figure 8 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Reinforcement process for high performance fiber paper based materials for foam forming.
[0026] Figure 2 It is the foaming device used in the present invention.
[0027] Figure 3 It is the molding device used in the present invention.
[0028] Figure 4 This is the "filler-binder-fiber" bonding form under the retention reinforcement system of Example 2.
[0029] Figure 5 To enhance the surface uniformity image of the foam forming paper sheet, the smaller the uniformity index is, the better the surface uniformity is.
[0030] Figure 6 These are electron microscope images of the paper sheets reinforced by impregnation and sintering in the present invention.
[0031] Figure 7 The pore size distribution and thermal weight loss curve of the reinforced paper sheet of the present invention are shown in FIG.
[0032] Figure 8 The actual object and electron microscope image of the foam-molded paper reinforced SiO2 aerogel composite material. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to specific examples, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0034] Reference Figure 2 A foaming device comprises a foaming barrel 3 having a baffle 2 surrounding the barrel wall counterclockwise and a stirring impeller 1 with three layers of arbitrarily adjustable gaps. The baffle can ensure the formation of high-intensity micro-turbulence during the stirring process, promote the dispersion of fibers in the barrel and the rapid generation of foam.
[0035] Reference Figure 3 , a foam-formed paper sheet forming device, the upper end 1 of the former is connected to a forming net 2 of a certain mesh number through screws 4, and a sealing gasket 3 is added to ensure sealing. The forming net 2 is inserted into the designed sealing gasket groove 3, and the lower drain port 6 is connected to an external steam-water separation device and a vacuum adjustment system. The vacuum adjustment system includes a pressure controller and a vacuum pump to perform dehydration and defoaming molding with controllable vacuum degree, and the liquid is discharged from the drain port 6 and can be recycled.
[0036] The raw materials used are all conventional commercially available materials without any processing, and there are no special requirements for the source of the raw materials.
[0037] The filler retention rate can be calculated by the weight change rate of the paper sheet. The filler retention rate is the mass of the paper sheet after molding divided by the mass of the fiber plus filler before molding.
[0038] Example 1 Preparation of unreinforced foam-formed quartz fiber paper: Step 1: In terms of mass concentration, weigh 0.83% (8.31 g / L) of 6 mm long chopped quartz fibers (fiber diameter is 7 μm) into a dispersion barrel, and add 0.5% PEO dispersant relative to the fiber mass, then add water to the initial foaming liquid volume of 1.8 L, and set the speed of the fiber disperser to 8000 rpm; add 0.5% PEO dispersant relative to the fiber mass and 2 g dodecyl dimethyl ammonium oxide surfactant to the stirred fiber slurry, and transfer the slurry to the foaming device.
[0039] Step 2: The foaming speed is set to 1800 rpm, and the foaming time is 10 min. After the foaming process, the slurry contains 60-70% air by volume, and the bubble radius is 20-80 μm. The foam slurry is then injected into the foam forming container, and the defoaming vacuum is set to 50 KPa. After dehydration and defoaming for 0.5 min, the foam-formed quartz fiber wet paper web is obtained.
[0040] Step 3: The foam-formed quartz fiber wet paper web is pressed and dried to obtain an inorganic fiber foam-formed paper base material, with a pressing pressure of 5 N and a drying temperature of 105°C.
[0041] Example 2 Enhanced retention system to improve foam-molded quartz fiber paper-based materials: Step 1: In terms of mass concentration, weigh 0.83% (8.31 g / L) of 6 mm long chopped quartz fibers (fiber diameter is 7 μm) into a deflaking barrel, and add 0.5% PEO dispersant relative to the fiber mass, then add water to the initial foaming liquid volume of 1.8 L, and set the speed of the fiber deflaker to 8000 rpm; after the deflaking, add the enhanced retention system (5% carboxymethyl cellulose relative to the fiber mass, 10% aluminum sol relative to the fiber mass and 1% anionic polyacrylamide relative to the fiber mass) to the slurry, mix well and stir in the fiber deflaker for 10 seconds, add 0.5% PEO dispersant relative to the fiber mass and 2 g dodecyl dimethyl ammonium oxide surfactant to the stirred fiber slurry, and transfer the slurry to the foaming device.
[0042] Step 2: The foaming speed is set to 1800rpm, and the foaming time is 10min. After the foaming process, the slurry contains 60-70% air by volume, and the bubble radius is 20-80 μm. The foam slurry is then injected into the foam forming container, and the defoaming vacuum is set to 50KPa. After dehydration and defoaming for 0.5min, a foam-formed high-performance fiber wet paper web is obtained.
[0043] Step 3: The foam-formed high-performance fiber wet paper web is pressed and dried to obtain a reinforced high-performance inorganic fiber foam-formed paper base material. The pressing pressure is 5N and the drying temperature is 105°C.
[0044] Example 3 Enhanced retention system to improve foam-forming quartz fiber paper-based materials: Step 1: Reduce the dosage of the inorganic crosslinking agent aluminum sol in the enhanced retention system to 5%, and the remaining operations remain the same as in Example 2.
[0045] Example 4 Carboxymethyl cellulose impregnated reinforced foam-molded quartz fiber paper-based material: Step 1: The preparation process of base paper before impregnation is consistent with that of Example 2.
[0046] Step 2: Carboxymethyl cellulose is an organic binder, and the concentration of the impregnation solution is 1.67 g / L (solid content of the adhesive solution is 6% relative to the fiber mass). First, the base paper is immersed in the impregnation solution for 30 minutes, and turned over every 5 minutes; after a period of impregnation, the impregnation solution is repeatedly sucked 4 times inside the molding mold (the vacuum degree is 10KPa) to pass through the foam-molded high-performance fiber paper sheet. After the suction, the paper sheet is air-dried for 30 minutes, and turned over every 2 minutes; the air-dried paper sheet is transferred to a 105℃ oven until the paper sheet is dry and taken out to obtain an impregnated reinforced high-performance inorganic fiber foam-molded paper base material.
[0047] Example 5 Hydroxypropyl cellulose impregnated and reinforced foam-molded high-performance fiber paper-based material: Step 1: The impregnation liquid is replaced with hydroxypropyl cellulose, and the concentration of the impregnation liquid is 5 g / L (solid content of the glue solution is 6% relative to the fiber mass). The other steps are consistent with Example 4.
[0048] Example 6: Methylcellulose impregnated and reinforced foam-molded high-performance fiber paper-based material: Step 1: The impregnation liquid was replaced with methyl cellulose, the concentration of the impregnation liquid was 5 g / L, and the other steps were consistent with Example 4.
[0049] Example 7 Polyvinyl alcohol impregnation reinforced foam forming high performance fiber paper base material: Step 1: The impregnation liquid is replaced with polyvinyl alcohol, and the concentration of the impregnation liquid is 5 g / L. The other steps are consistent with Example 4.
[0050] Example 8 Carboxymethyl cellulose and silica sol reinforced foam-molded high-performance fiber paper-based material: Step 1: The impregnation liquid is replaced with a mixture of carboxymethyl cellulose and silica sol, wherein the concentration of carboxymethyl cellulose is 2.5 g / L and the concentration of silica sol is 5.63%. The other steps are consistent with Example 4.
[0051] Example 9: Foam-molded high-performance fiber paper-based material reinforced by compounding polyvinyl alcohol and silica sol: Step 1: Replace the impregnation liquid with a mixture of polyvinyl alcohol and silica sol, wherein the concentration of the polyvinyl alcohol impregnation liquid is 8.3 g / L, and the concentration of the silica sol is 5%. The other steps are consistent with Example 4.
[0052] Example 10: Foam-molded high-performance fiber paper-based material reinforced by compounding polyamide polyamine epichlorohydrin resin with silica sol: Step 1: Replace the impregnation liquid with a mixture of polyamide polyamine epichlorohydrin resin and silica sol, wherein the concentration of the polyamide polyamine-epichlorohydrin resin impregnation liquid is 2.5%, and the concentration of the silica sol is 7.5%. The other steps are consistent with Example 4.
[0053] The performance tests of the high-energy fiber paper-based materials prepared in Examples 1-9 are shown in Table 1 below.
[0054] Table 1 From the results in Table 1, it can be seen that the foam-formed fiber paper-based material prepared in Example 1 of the present invention (without the reinforcement retention system) has no strength after drying. After being treated with Example 2 (with the reinforcement retention system), the obtained high-performance fiber paper-based material has processable strength, a complete structure in the subsequent impregnation liquid, and good wet strength (see Figure 4 ); In order to further enhance the strength of the foam-formed paper sheet of Example 2 (enhanced retention system), Examples 4-10 were used for impregnation enhancement. The strength of the enhanced paper sheet was significantly improved, and the tensile strength and surface uniformity were significantly improved compared with the commercially available inorganic fiber paper sheet (see Figure 5 , Figure 6 ), and the pore size distribution of the paper sheet after impregnation reinforcement is still slightly larger than that of the wet-formed paper sheet, and the adhesive component does not cause blockage of the internal pore structure inside the reinforced paper sheet, that is, the above-mentioned reinforcement method not only gives the paper sheet good structural strength, but also does not affect the subsequent impregnation processing of the paper sheet to prepare high-performance composite materials ( Figure 7 a).
[0055] Comparative Example 1 Sintering-enhanced wet-formed inorganic fiber paper-based material: Step 1: In terms of mass concentration, 0.83% (8.31 g / L) of 6 mm long chopped quartz fibers (fiber diameter is 7 μm), 10% of glass powder relative to the fiber mass, and 5% of boron carbide powder relative to the fiber mass were weighed into a deflaking barrel, and 0.5% of PEO dispersant relative to the fiber mass was added. Then water was added to the initial foaming liquid volume of 1.8 L, and the speed of the fiber deflaker was set to 8000 rpm; 5% of carboxymethyl cellulose, 10% of aluminum sol, and 1% of anionic polyacrylamide were added to the slurry after deflaking, and the mixture was mixed and deflaked in the fiber deflaker for 10 seconds; 0.5% of PEO dispersant was added to the deflaked slurry, and the mixture was transferred to a rapid prototyping device and filled with water to a total volume of 8 L.
[0056] Step 2: The formed wet paper web is pressed and dried to obtain the high-performance fiber preform, the pressing pressure is 5N, and the drying temperature is 105°C.
[0057] Step 3: The dried foam-formed high-performance fiber paper sheet is placed in a muffle furnace and sintered at 900 °C for 2 h.
[0058] Example 11 Sintered enhanced foam-molded inorganic fiber paper-based material: Step 1: In terms of mass concentration, 0.83% (8.31 g / L) of 6 mm long chopped quartz fibers (fiber diameter is 7 μm), 10% of glass powder relative to the fiber mass, and 5% of boron carbide powder relative to the fiber mass were weighed into a deflaking barrel, and 0.5% of PEO dispersant relative to the fiber mass was added. Then water was added to the initial foaming liquid volume of 1.8 L, and the speed of the fiber deflaker was set to 8000 rpm; 5% of carboxymethyl cellulose, 10% of aluminum sol, and 1% of anionic polyacrylamide were added to the slurry after deflaking, and the mixture was mixed and deflaked in the fiber deflaker for 10 s; 0.5% of PEO dispersant and 2 g of dodecyl dimethyl ammonium oxide surfactant were added to the deflaked slurry, and the slurry was transferred to the foaming device.
[0059] Step 2: The foaming speed is set to 1800 rpm, and the foaming time is 10 minutes. After the foaming process, the slurry contains 60-70% air by volume, and the bubble radius is 20-80 μm. The foam slurry is then injected into the foam forming container, and the defoaming vacuum is set to 50 KPa. After dehydration and defoaming for 0.5 minutes, a foam-formed high-performance fiber wet paper web is obtained.
[0060] Step 3: The high-performance fiber wet paper web formed by foam is pressed and dried to obtain the high-performance fiber preform, the pressing pressure is 5N, and the drying temperature is 105°C. It is worth noting that compared with the foam-formed paper sheet without the addition of the enhanced retention system, the filler retention rate inside the paper sheet at this stage is increased from 75% to 87%.
[0061] Step 4: The dried foam-formed high-performance fiber paper sheet is placed in a muffle furnace and sintered at 900°C for 2 hours.
[0062] Example 12 Sintered enhanced foam-molded inorganic fiber paper-based material: Step 1: Replace the filler with 15% boron carbide powder relative to the absolute dry fiber mass, and the other steps remain the same as Example 11.
[0063] Example 13 Sintered enhanced foam-molded high-performance fiber paper-based material: Step 1: Replace the filler with glass powder at 10% of the absolute dry fiber mass. The other steps remain the same as in Example 11.
[0064] Table 2 From the results in Table 2, it can be seen that the inorganic fiber paper sheets of Examples 11-13 of the present invention have good paper sheet strength and high temperature resistance after sintering at 900°C. Experiments have shown that the thermogravimetric loss rate of the paper sheets under this reinforcement method at 800°C (refer to GB / T 27761-2011) is less than 3% (see Figure 7 b). The comparison results of comparative example 1 and examples 11-13 show that the retention and reinforcement method is obviously more suitable for inorganic fiber paper sheets formed by foam. The strength of inorganic fiber foamed paper sheets after retention and sintering reinforcement is ( Figure 6 )、Evenness( Figure 5 ) and high temperature resistance ( Figure 7 b) are significantly better than wet-formed paper sheets and commercially available ceramic fiber samples.
[0065] Comparative Example 2: Enhanced retention system to improve foam-molded quartz fiber paper-based material: Step 1: The enhanced retention system was replaced with 5% carboxymethyl cellulose, 10% silica sol, and 1% polyethylene oxide, and the remaining operations were consistent with Example 2.
[0066] Comparative Example 3: Traditional wet molding retention system improves foam molding quartz fiber paper-based material: Step 1: In terms of mass concentration, weigh 0.83% (8.31 g / L) of 6 mm long chopped quartz fibers (fiber diameter is 7 μm) into a deflaking barrel, and add 0.5% PEO dispersant relative to the fiber mass, then add water to the initial foaming liquid volume of 1.8 L, and set the speed of the fiber deflaker to 8000 rpm; after deflaking, add the enhanced retention system (5% carboxymethyl cellulose relative to the fiber mass, 10% aluminum sol relative to the fiber mass, and 1% anionic polyacrylamide relative to the fiber mass) to the slurry, mix well, and stir in the fiber deflaker for 10 seconds, add 0.5% PEO dispersant to the deflaked slurry, and transfer it to the rapid prototyping device, and add water to the total volume of 8 L.
[0067] Step 2: The formed wet paper web is pressed and dried to obtain the high-performance fiber preform, the pressing pressure is 5N, and the drying temperature is 105°C.
[0068] Table 3 From the results in Table 3, it can be seen that the enhanced retention system of Example 2 of the present invention has the best effect. After reducing the amount of the inorganic crosslinking agent, the strength of the paper sheet decreases slightly. For example, in Comparative Example 2, after replacing the inorganic crosslinking agent with silica sol, it interacts with the fiber sizing agent polyethylene oxide, the fiber dispersion effect deteriorates, the paper sheet uniformity deteriorates significantly, and the paper sheet strength is low (such as Figure 5 As shown in Comparative Example 3, the retention and reinforcement system flocculates the reinforcing agent around the fiber, and fiber flocs are formed before molding. Unlike foam molding, wet molding does not have the stirring and foaming process, and the fiber flocs will not be dispersed, and the uniformity of the molded paper sheet is extremely poor. Therefore, this reinforcement retention system is not suitable for the traditional wet molding process, but is suitable for the foam molding process (such as Figure 4 , Figure 5 ).
[0069] Example 14 Preparation of Inorganic Fiber Silica Aerogel Composite Material Preparation process: The retention reinforcement-SiO2 aerogel composite material is prepared by the sol-gel method. The foam molding base paper after the reinforcement treatment in Example 2 is immersed in 15% silica sol. After aging (40°C 48h), modification (hydrophobic agent trimethylchlorosilane, hydrophobic agent mass 10%, 80°C, 48h), and carbon dioxide supercritical drying, the foam molding base paper reinforced silica aerogel composite material can be obtained.
[0070] like Figure 8 As shown, thanks to the good strength, excellent uniformity and rich pore structure of the foam molding base paper, the prepared SiO2 aerogel composite material has better mechanical strength and thermal insulation properties.
[0071] The sol-gel method was adopted to prepare a retention-aid sintering reinforcement-SiO2 aerogel composite material. The foam molding base paper after sintering and reinforcement treatment in Example 11 was immersed in 15% silica sol. After aging (40°C 48h), modification (hydrophobic agent trimethylchlorosilane, hydrophobic agent mass 10%, 80°C, 48h), and carbon dioxide supercritical drying, the foam molding base paper reinforced silica aerogel composite material was obtained.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A microparticle enhancement-retention system, characterized in that: The invention is composed of an organic binder, an inorganic crosslinking agent and a fiber sizing agent, wherein the mass ratio of the organic binder, the inorganic crosslinking agent and the fiber sizing agent is 1-10:5-15:0.1-5.
2. A particle enhancement-retention system according to claim 1, characterized in that: The organic binder is carboxymethyl cellulose or hydroxypropyl cellulose; The inorganic cross-linking agent is aluminum sol or silica sol; The fiber sizing agent is at least one of anionic polyacrylamide, polyethylene oxide, and cationic polyacrylamide.
3. A method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material using the microparticle reinforcement-retention system according to claim 1 or 2, characterized in that: The following steps are involved: (1) Dispersing inorganic fibers, fiber dispersant, microparticle reinforcement-retention system and water uniformly, adding fiber dispersant and surfactant and mixing uniformly to obtain a foaming initial solution; (2) The initial foaming liquid is transferred to the foaming device, and the foam slurry is obtained after a certain stirring speed and time. The foam slurry is then injected into the rapid prototyping device, and the wet paper web is obtained after vacuum dehydration and defoaming. After pressing and drying, a reinforced high-performance inorganic fiber foam molding paper base material is obtained.
4. The method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material according to claim 3, characterized in that: The inorganic fiber is at least one of alumina fiber, quartz fiber, glass fiber, and aluminum silicate fiber cotton, with a fiber diameter of 5-18 μm and a length of 6-36 mm. The inorganic fiber concentration in the initial foaming liquid is 5-10 g / L; The solid contents of the organic binder, the inorganic crosslinking agent and the fiber sizing agent in the particle retention reinforcement system are 1-10%, 5-15% and 0.1-5% of the absolute dry fiber mass, respectively; The surfactant is at least one of sulfate ester salts, cationic amine salts, cationic quaternary ammonium salts, and betaine polyvinyl alcohol, and the surfactant concentration in the initial foaming liquid is 0.5-5 g / L.
5. The method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material according to claim 3, characterized in that: In step (2), the stirring speed is 1500-2000 rpm and the stirring time is 8-15 min; The air content of the foam slurry is 55%-75%, and the average bubble diameter is 20-100 μm; The vacuum degree of the dehydration and defoaming is 5-70 KPa, and the squeezing pressure is 5-80N.
6. The method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material according to any one of claims 3 to 5, characterized in that: The preparation method further comprises the following steps: impregnating the reinforced high-performance inorganic fiber paper foam molding base material in step (2) in an impregnation liquid to obtain an impregnated reinforced high-performance foam molding inorganic fiber paper base material; The impregnation liquid is an organic impregnation liquid and / or an inorganic impregnation liquid, the mass concentration of the organic impregnation liquid is 0.1%-5% or 0.1-10g / L, and the mass concentration of the inorganic impregnation liquid is 0.5%-15%; The organic impregnation liquid is at least one of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, polyamide polyamine-epichlorohydrin resin, and polyvinyl alcohol solution; The inorganic impregnation liquid is at least one of aluminum sol, silica sol and sodium silicate solution.
7. The method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material according to any one of claims 3 to 5, characterized in that: In the step (1), fillers are also added, and finally the reinforced high-performance foam-molded inorganic fiber paper-based material obtained in the step (2) is sintered at a high temperature to obtain a sintered reinforced high-performance foam-molded inorganic fiber paper-based material; The filler is at least one of glass powder, boron carbide, boron nitride and silicon dioxide aerogel powder, and the amount of the filler is 5%-30% of the mass of the absolute dry fiber.
8. The method for preparing a reinforced high-performance inorganic fiber foam forming paper-based material according to claim 7, characterized in that: The high temperature sintering temperature is 700-900° C., and the sintering time is 1-2 h.
9. A reinforced high-performance inorganic fiber foam forming paper-based material, characterized in that: Prepared by the method described in any one of claims 3 to 8.
10. Use of the reinforced high-performance inorganic fiber foam molding paper-based material according to claim 9 in the preparation of a silica aerogel composite material.